Bridging the global and the local in rural and regional planning: insights from a deliberative approach to visioning future sustainability in the Greater Geraldton City Region. - Armstrong, Rachel; Hartz-Karp, Janette; Marinova, Dora (University of Western Australia, 2011)
The Greater Geraldton City Region is undergoing a period of rapid change. This creates a complex challenge for local and regional planning. In particular, how the people in the region understand what is facing them, their willingness to go along with those plans and their potential agency in adapting plans to meet their needs and aspirations. Emerging opportunities, such as the Oakagee Port and Rail Development and Australian Square Kilometre Array Pathfinder (ASKAP) will bring significant change to the regional economy and population. They also have potential to alter the social fabric of the community, especially the small town feel of Geraldton. Responding to the global challenge of climate change, the region has significant potential for renewable energy industries to support transition towards becoming carbon neutral. This paper considers the regional development context for the Greater Geraldton City Region, how it is being planned, and how community understands the global and local prospects, and incorporates them into their vision of the future. Preliminary outcomes from deliberative, collaborative participation of local people in the future planning of the Greater Geraldton City-Region through the ‘2029 and Beyond: Sustainable Future City’ project are presented. By carefully considering the opportunities and challenges presented by the big issues that are global in their reach, participants have identified key directions for the future, including local social and cultural issues that need to underpin future planning and development to ensure the sustainability of the community. It is proposed that the outcomes from deliberative planning so far contribute to a more holistic approach to regional planning that bridges local values with the global drivers of regional development.